2020
DOI: 10.3847/1538-4357/abad36
|View full text |Cite
|
Sign up to set email alerts
|

Secular Gravitational Instability of Drifting Dust in Protoplanetary Disks: Formation of Dusty Rings without Significant Gas Substructures

Abstract: Secular gravitational instability (GI) is one promising mechanism for creating annular substructures and planetesimals in protoplanetary disks. We perform numerical simulations of secular GI in a radially extended disk with inwardly drifting dust grains. The results show that, even in the presence of dust diffusion, dust rings form via secular GI while the dust grains are moving inward, and the dust surface density increases by a factor of 10. Once secular GI develops into a nonlinear regime, the total mass of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 90 publications
5
52
0
Order By: Relevance
“…The depletion of dust at low viscosity creates inner cavities. These cavities are observed in several disks (Espaillat et al 2014;van der Marel et al 2018) and are described as wide regions in disks where there is no emission observed and therefore possibly no dust present. These cavities can be explained by the presence of planets: either one giant planet is large enough to block the dust flux from the outer disk and the inner disk empties by radial drift; or multiple planets are present and large enough to create a wide common gap.…”
Section: Solar System Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The depletion of dust at low viscosity creates inner cavities. These cavities are observed in several disks (Espaillat et al 2014;van der Marel et al 2018) and are described as wide regions in disks where there is no emission observed and therefore possibly no dust present. These cavities can be explained by the presence of planets: either one giant planet is large enough to block the dust flux from the outer disk and the inner disk empties by radial drift; or multiple planets are present and large enough to create a wide common gap.…”
Section: Solar System Configurationsmentioning
confidence: 99%
“…Recent observations with the Atacama Large Millimeter/Submillimeter Array (ALMA) and the Spectro-Polarimetric High-contrast Exoplanet REsearch (SPHERE) instruments show protoplanetary disks that present different kinds of substructures (rings, gaps, cavities, and asymmetries) present in the gas (e.g., Teague et al 2018;Pinte et al 2020) and in the dust (e.g., ALMA Partnership et al 2015;Avenhaus et al 2018;Andrews et al 2018). These substructures may have different possible origins, including: self-induced dust traps due to dust growth and dust backreaction on the gas (Gonzalez et al 2017), dust growth in snow lines (Zhang et al 2015), zonal flows (Flock et al 2015), secular gravitational instabilities (Takahashi & Inutsuka 2016;Tominaga et al 2020), sintering-induced rings (Okuzumi et al 2016), and gap opening embedded planets (Pinilla et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a significant amount of large dust whose Stokes number is close to unity refluxed to disk provides an ideal condition for the growth of the secular gravitational instability (SGI) (Takahashi & Inutsuka 2014Tominaga et al 2018Tominaga et al , 2020 that are expected to be a powerful mechanism for creating ring and planetesimals in the outer region of the disk. Since SGI creates many axisymmetric dusty ring structures in the disk and may subsequently create planetesimals, a combination of the ash-fall and subsequent SGI can be an explanation for multiple ring-like structure observed in protoplanetary disks (ALMA Partnership et al 2015;Fedele et al 2017;Andrews et al 2018;Fedele et al 2018;Long et al 2018).…”
Section: Implications For Planet Formationmentioning
confidence: 99%
“…Other processes have been proposed for assembling planetesimals from dust. For example, turbulent clustering of dust, leading directly to gravitational collapse (Cuzzi et al 2001(Cuzzi et al , 2008(Cuzzi et al , 2010Chambers 2010;Hopkins 2016;Hartlep & Cuzzi 2020), or the concentration of selfgravitating clumps of dust in pressure traps or zonal flows (Whipple 1972;Johansen et al 2009a;Bai & Stone 2014;Riols & Lesur 2018), vortices (Barge & Sommeria 1995;Lyra et al 2008), and secular gravitational instability (Sekiya 1998;Youdin 2011;Michikoshi et al 2012;Takahashi & Inutsuka 2014;Tominaga et al 2018Tominaga et al , 2020 are alternate routes to planetesimal formation. The difference in the underlying physics between these planetesimal formation scenarios leads to different requirements placed on the dust evolution processes in the molecular cloud, star formation, and protoplanetary discs feeding into them.…”
Section: Introductionmentioning
confidence: 99%